Representation of Delinquent Juveniles (Yankee) in Japan in Two Japanese Movies - Linda Unsriana; Trifena Agatha Hariyanto (IZUMI, 2022)
Yankee, which is a group of delinquent juveniles in Japan makes the society tend to focus only on the bad things they do. However, one of the interesting things about Yankee is that they stick to the concept of shuudan ishiki – the concept of group awareness that has been upheld by Japanese society for a long time. Therefore, this study aimed to analyze the representation of Yankee in “Gokusen: The Movie” and “Drop”, from the appearance, behavioral, and group consciousness aspects. The method used in this study was an in-depth observation of the data corpus, then the analysis was carried out with the descriptive analysis method. To analyze the data, the theory of Sociology of Literature by Wellek & Warren and the theory of Representation by Stuart Hall were used. The shuudan ishiki concept was also used to analyze the behavior of the characters. The results showed that the appearance and behavior of students who become Yankees deviate from the customs, regulations, and norms that are applied in society. Other than that, the Yankee group in each movie has a high group awareness, which is portrayed by the loyalty and solidarity among the group members.     gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor